Madrid, 1900-2010: Guía de Urbanismo y Diseño Urbano - Ramírez Serpa, Iván (2019)
The following review gives the opportunity to talk about heritage in its integral conception, in this chance about the particular case of Madrid's urban landscape and how it has gradually been forgedduring the last two centuries, according to a specific practice of planning. The virtue of the publication consists precisely in describing and analyzing representative urban pieces that make up the current patrimonial landscape of the city: streets, squares, gardens, residential buildings, facilities,infrastructures, uses of public space, etc. It differs meritoriously from those traditional architectural guides that only contemplate the isolated object, indifferently from its surroundings, without thinking about the city as it is perceived by the neighbor, the passer-by, the student.